Lost Worlds Latin America and the Imagining of Empire - Foster, Kevin (Pluto Press, 2009)
Think of Latin America and what do you see? Escape? Adventure? Chaos? Oblivion? Lost Worlds explores how these stereotypes came into being and what they tells us about ourselves. Examining a range of texts, from Southey's epics to Naipaul's essays, from Conan Doyle's gentlemen adventurers to Kerouac's restless hipsters, this book reveals the role that Latin America has played in British, US and Australian endeavours in the nineteenth and twentieth centuries. Over the last 200 years, Latin America has served the West as an imaginary realm where its highest hopes and deepest anxieties might be realised.